Participatory Action Research: Maternal and Child Health System - Anshori, Mohamad Alif Irfan; Lestari, Astri Puji; Devi, Kiki Amelia (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2019)
The birth of a child is basically very much awaited in every family. In order for the mother to be safe and the child to be born healthy, she must perform antenatal care routinely to the obstetrician or to the midwife. The longer the gestational age, the fetus will also grow and develop, so if not carried out proper supervision can cause problems both during pregnancy, at the time of delivery, even childbirth, and the worst can result in death of mother and baby. Pregnancy screening is also an effort to reduce maternal mortality. The frequency of antenatal care is used to assess the use of antenatal services in quantity. The higher the coverage of antenatal care, the more likely the process of pregnancy and childbirth can be carried out properly. So that the examination of the womb during pregnancy is something that should not be missed and underestimated. In the obstetric examination the doctor or midwife will tell about the health of the fetus, fetal development, nutrition or any good food consumed during pregnancy, how to set a healthy diet for pregnant women, various exercise tips and healthy life that supports fetal growth and counting estimated date of birth of the baby. The estimated date of birth of a baby is not always the same as the birth. Not a few who turned out to give birth before the estimated date and not a few also gave birth after the estimated date. From the problems, the solution to overcome this is that an Android-based application can be made that can connect between midwives and expectant mothers and can search for the nearest midwife. With this application, it is expected to help make it easier for mothers and midwives to find out the growth record of the fetus while in the womb and facilitate the mother in the process of giving birth, especially during emergencies so that the mother will be immediately addressed by the nearest midwife and is expected to minimize the maternal mortality rate and baby during childbirth. Based on acceptance tests conducted on several users, it can be concluded that 84.3% of users agree that the application of "Sehati" is useful to support the health of pregnant women and children with an easy-to-understand appearance. Other statements include 9.1% neutral, and 6.6% disagree.